National industrial sectors: economic and energy characteristics - Cherevatskyi, D.; Soldak, M.; Cheylyakh, D. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
The article explores the integrated relationship between the economic and energy dimensions of industrial performance, with a particular focus on the position of Ukraine’s industrial sector in the global context. Although major international institutions systematically publish extensive datasets – including industrial value added (World Bank) and industrial consumption of primary energy resources (IEA) – these two informational domains remain largely disconnected at the analytical level. The absence of a unified sector-specific indicator analogous to “energy intensity” for industry forms a significant gap in assessing cross-country industrial efficiency and structural competitiveness. The study proposes an approach to evaluating the economic–energy efficiency of national industrial systems by combining data on industrial value added with corresponding volumes of primary energy consumption. Using econometric methods with temporal and spatial resolution, the authors compare Ukraine with a wide range of world economies, including technological leaders. The results demonstrate that even in the pre-war year 2021, Ukraine exhibited one of the lowest levels of industrial energy efficiency globally. Such disproportions have critical implications for the country’s economic resilience and energy security, especially under wartime conditions marked by damaged energy infrastructure and limited access to fuel resources. The findings underline the necessity of profound industrial restructuring in Ukraine aimed at reducing energy intensity and improving the metabolic efficiency of industrial production. The proposed analytical framework can support the formulation of modern industrial policy and serve as a methodological basis for further interdisciplinary research at the intersection of industrial economics and energy studies.